Dobro jako wartość aksjologiczna (na przykładzie przekazów medialnych dotyczących pandemii COVID-19) = Good as axiological value (example of media coverage of the COVID-19 pandemic) - Bedka, Aleksandra (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
As one of the axiological values, goodness together with truth and beauty form transcendental elements that interpenetrate and influence each other in every aspect of life. The COVID-19 pandemic provided an opportunity to observe people`s attitudes towards others, the desire to work for the sick and the needy. The media show different reactions of the population to those in need - from disrespectful behaviour to civil society organisations. In the face of a global tragedy, man is tested for his values: he can follow the call of the people or suppress all feelings within him.
Keywords: aksjologia; Bóg; COVID-19; koronawirus; pandemia; czyn; pomoc; człowiek; axiology; thegood; God; coronavirus; pandemic; actions; help; human